Hukuman Mati Perspektif Al-Qur'an - Herry, Musleh (el Harakah: Jurnal Budaya Islam, 2003)
The problem of capital punishment in Indonesia as a country which has Pancasila philosophy is still a discussion which caused many different views until now. This problem arises because it is considered to be "violating" human rights, it is seen from the history of punishment that the death penalty was born together with the birth of man on the face of the earth, with the legal culture of "retalism" like wolves eating wolves, in which the criminal is based on the theory of absolute revenge (absolute theory) .The death penalty in terms of Islamic religion (Shari'at Islam) death is a penalty stipulated by Shari'a Islam with the decree of Allah SWT which can not be inviolable by anybody.Only what we need to learn in this case is the terms of its implementation so as not to easily impose the judgment of the law. means that according to Islamic views, the death penalty is merupaka n criminal offenses that are formally required to be held. The death penalty that is done according to the correct Islamic religious provisions is not: contrary to the philosophy of the State, is not: contrary to the elements of Belief in God Almighty, because Islamic sha'at is a Shari'ah based on Belief in the One Supreme. Masalah hukuman pidana mati di Indonesia sebagai suatu negara yang mempunyai falsafah Pancasila, masih merupakan suatu pembicaraan yang banyak menimbulkan berbagai perbedaan pandangan sampai sekarang Permasalahan ini muncul karena dianggap "melanggar'' hak asasi manusia. Ditinjau dari sejarah pemidanaan, bahwa hukuman mati lahir bersamasama dengan lahirnya manusia di muka bumi ini, dengan budaya hukum "retalisme" bagaikan serigala memakan serigala. Mada masa itu berlaku pidana berdasarkan pada teori pembalasan mutlak (teori absolut). Hukuman mati ditinjau dari segi agama Islam (Syari'at Islam) sudah jelas bahwa hukuman mati itu adalah pidana yang ditetapkan oleh Syari' at Islam dengan dekrit Allah Swt yang sama sekali tidak boleh diganggu gugat oleh siapapun juga. Hanya yang perlu kita pelajari dalam hal ini adalah syarat-syarat pelaksanaannya agar tidak dengan mudah menjatuhkan putusan hukum itu. Hal ini berarti bahwa menurut tinjauan agama Islam, maka hukuman mati itu adalah merupakan pidana yang secara resmi perlu diadakan. Hukuman mati yang dilakukan menurut ketentuan-ketentuan agama Islam yang benar adalah tidak: bertentang dengan falsafah Negara, tidak: berlawanan pula dengan unsur-unsur Ketuhanan Yang Maha Esa, karena syai'at Islam mempakan syari'at yang berdasarkan Ketuhanan Yang Maha Esa.